STRATEGI BAURAN PROMOSI DALAM MENINGKATKAN JUMLAH MAHASISWA BARU TAHUN AKADEMIK 2017/2018 POLITEKNIK TMKM KARAWANG - Taufan Gojali (Media Mahardhika, 2019)
Basically promotion needs at an educational of institution. Remember, market development and competition more strict. Promotion of strategy to be spearhead a marketing plan. That is more impotant in an educational of institution. The educational of institution has been planning the purpose, and can to do that. Author researched at Politeknik TMKM. The purpose of research knowed the strategy and implementation of promotion activities at the Politeknik TMKM. The subject in research was Director of Politeknik TMKM and Team of Promotion New Student Reception as information. The object was about implementation promotion, its limited on promotion of Politeknik TMKM at 2017/2018. The method used qualitative descriptive, it described and analized data was collected. And than data collection method was interview and documentation. The result research described method of promotion mix strategy. The promotion mix staretgy used combination of promotion, like as personal selling, mass selling, sales promotion, public relations, and direct marketing. Publication of media used socialization or presentation in front of class with brochure and questionnaire as promotion support, scolarship program and banner. The receiption of new student was hoped to increase used promotion tools and publication media in 2017/2018 year as many as 200%.